Experimental Study of Dynamic Mechanics Characteristics of Saturated Marble under Low Temperature - Yang Yang; Jianguo Wang (Shock and Vibration)
The effect of low temperature on dynamic mechanical properties of low-temperature frozen marble at a high strain rate was studied by a dynamic impact test. The influence of temperature changes (25°C–40°C), especially negative temperature changes, on dynamic strength, peak strain, and failure mode of the marble was analyzed. Combined with the fracture morphology, the reasons for the deterioration of dynamic mechanical strength of water-saturated marble at lower negative temperatures were investigated. The experimental results show that the dynamic mechanical properties of marble are significantly affected by the change of freezing temperature. The dynamic strength firstly decreases and then increases with the decrease of temperature in the range of 25°C to −20°C, but the dynamic strength decreases sharply after −20°C. The peak strain increases first, then decreases, and then increases, and the inflection point temperature of the change is −5°C and −20°C, respectively, which is completely different from the static load test results of frozen rock at low temperature. According to fracture morphology analysis, water-ice phase transformation at −5°C leads to the nucleation and expansion of a large number of microcracks and micropores in marble, and the interaction between slip separation cracks and microstructures caused by shear deformation under impact separates the massive crystals inside the rock into microscopic crystals, thus reducing the bearing capacity and strength of marble. From −5°C to −20°C, the ice medium and marble matrix contract when cooled, and the microcracks and micropores caused by the phase transition gradually close during the contraction process, the integrity of the rock is restored, and the dynamic strength of the rock is increased. At −20°C, there is a great difference in the shrinkage rate of the marble matrix and the ice medium, and the internal microstructure increases. Meanwhile, the impact amplifies the brittleness of the rock at low temperatures, leading to a sharp decrease in the dynamic strength of the marble.